Are there differences between Mediterranean diet and the consumption of harmful substances on quality of life?—an explanatory model in secondary education regarding gender - Melguizo-Ibáñez, Eduardo; Zurita-Ortega, Félix; Ubago-Jiménez, José Luis; Badicu, Georgian; Yagin, Fatma Hilal; González-Valero, Gabriel; Ardigò, Luca Paolo; Puertas-Molero, Pilar (Frontiers in Nutrition, 2023)
Background: Adolescence is a key life stage in human development. It is during this stage of development that healthy and physical behaviors are acquired that will last into adulthood. Gender differences in the acquisition of these behaviors have been observed. This research aims to (a) study the levels of Mediterranean diet adherence, quality of life and alcohol and tobacco consumption as regarding the gender of the participants and (b) study the effects of the variable adherence to the Mediterranean diet, alcohol consumption and tobacco consumption on quality of life as a function of the gender of the participants.A non-experimental, cross-sectional, exploratory study was carried out in a sample of 1057 Spanish adolescents (Average AgeM=14.19; Standard DeviationS.D = 2.87).The comparative analysis shows that the male teenagers shows a higher Mediterranean diet adherence compared to the male adolescents (p ≤ 0.05) and a higher consumption of alcoholic beverages (p ≤ 0.05). On the contrary, adolescent girls show a higher consumption of alcoholic beverages than male participants (p ≤ 0.05). In contrast, the female teenagers show a higher Formatiert: Block